Understanding public perceptions and intentions to use traditional versus emerging investment platforms : the effect of message framing and regulatory focus theory on the technology acceptance model - Lim, Vera Si Hui (Nanyang Technological University, 2022)
With the rise of blockchain technology, asset tokenisation – issuing blockchain tokens to represent asset ownership – is expected to become more prevalent. This study uniquely proposes that tokenised health data could serve as a digital currency for the purchase of tokenised financial assets, and draws upon technology acceptance model, framing, and gamification to examine the Singapore public’s acceptance of such emerging platforms compared to traditional investment platforms. We test how message framing (through promotion-prevention message frames and gamification) influence perceived ease of use and perceived usefulness of traditional investment versus asset tokenisation platforms, and how regulatory fit and risk propensity moderates these main effects. Using a 2 (promotion-focused versus prevention-focused message frame) × 2 (gamification versus non-gamification) × 2 (traditional investment versus asset tokenisation platform) between-subject factorial design, results showed that when users’ regulatory orientation and the message frame match, the investment platform’s perceived risk is lowered. Risk-taking users perceive gamified investment platforms as easier to use and useful, and vice versa for risk-averse participants. Gamified platforms were perceived as easier to use. Prevention-frame messages led to higher perceived risk than promotion-frame. The findings provide future direction in tailoring more effective messaging to influence attitudes and intentions towards investment platforms.